Northward Expansion of Desert Climate in Central Asia in Recent Decades. Issue 11 (6th June 2022) - Hu, Qi; Han, Zihang
Abstract: Climate variation in Central Asia is examined using changes of climate classification to obtain geographically specific information of the variation across the region. Major results show the northward expansion of desert climate by over 100 km in mid‐latitudes of the region since the 1980s. In the meantime, all types of climates in the region have increased temperatures. In mountainous areas, previous cold climate is replaced by warmer and also wetter climate. These changes could have largely resulted in the fast retreat of glaciers and the temporary rise of groundwater and the water levels of lakes in the drainage areas in recent decades. Because different climate types are associated with specific flora and fauna, the shifts of the climate types in locations have elevated the potential to initiate new feedbacks of the ecological systems to the climate and complicate its variation. Plain Language Summary: Over 60% of Central Asia has arid‐to‐semiarid climate. In such climate, food production and natural resources availability are particularly sensitive to variations of the climate. Even marginally dry years have resulted in substantial losses of agricultural yields, devastating local economy and threatening countries' finances and societal stability. It is thus important to understand how the climate in the region has been varying and which direction the variation is taking to. These are the questions addressed in this study. The method used is climate classification and major results are as given below. (a) The desert climate has expanded northward by over 100 km in the mid‐latitudes Central Asia since the 1980s, (b) all the climate types in Central Asia have increased their mean temperatures in the same period, and (c) in mountainous areas, the previous cold climate has been replaced by warmer and also wetter climate. Economic and societal impacts of these changes include contracting agricultural lands and subsequent food production potential, diminishing glaciers, and changes of the seasonality of precipitation. Because different climate types have their associated flora and fauna these changes are also transforming the region's ecosystems. Key Points: Desert climate has expanded northward by over 100 km in mid‐latitudes Central Asia since the mid‐1980s Previously cold climate in high elevation areas has been replaced by warmer and wetter climate that is transforming the region's hydrology